The impact of information and communication technology on VMI performance - Radzuan, Kamaruddin; Othman, Siti Norezam; Mohamed Udin, Zulkifli; Omar, Mohd Faizal; Yaakob, Mazri (2014)
The aim of this paper is to examine the impact of information and communication technology dimensions namely information sharing, quality of information, and compatibility of information system towards VMI performance.Questionnaire was the main instrument for the study and it was gathered from 101 of suppliers in manufacturing companies.The findings show that information sharing and quality of information system contributes to service performance.Meanwhile, only quality of information system contributes to cost performance.Although, literature suggest that information sharing, quality of information, compatibility of information system have a positive impact on both cost reduction and service improvement in VMI program, this study shows that there is a limited effect on cost performance. In fact, compatibility of information system has not played any major role to increase performance of VMI program.This study recommends that the supplier should urge their customer to share demand information through the quality of information system.